Overexpression of a novel cold‐responsive transcript factor LcFIN1 from sheepgrass enhances tolerance to low temperature stress in transgenic plants. Issue 3 (3rd August 2015) - Gao, Qiong; Li, Xiaoxia; Jia, Junting; Zhao, Pincang; Liu, Panpan; Liu, Zhujiang; Ge, Liangfa; Chen, Shuangyan; Qi, Dongmei; Deng, Bo; Lee, Byung‐Hyun; Liu, Gongshe; et al.
Summary: As a perennial forage crop broadly distributed in eastern Eurasia, sheepgrass ( Leymus chinensis (Trin.) Tzvel) is highly tolerant to low‐temperature stress. Previous report indicates that sheepgrass is able to endure as low as −47.5 °C, allowing it to survive through the cold winter season. However, due to the lack of sufficient studies, the underlying mechanism towards the extraordinary low‐temperature tolerance is unclear. Although the transcription profiling has provided insight into the transcriptome response to cold stress, more detailed studies are required to dissect the molecular mechanism regarding the excellent abiotic stress tolerance. In this work, we report a novel transcript factor LcFIN1 ( L. chinensis freezing‐induced 1) from sheepgrass. LcFIN1 showed no homology with other known genes and was rapidly and highly induced by cold stress, suggesting that LcFIN1 participates in the early response to cold stress. Consistently, ectopic expression of LcFIN1 significantly increased cold stress tolerance in the transgenic plants, as indicated by the higher survival rate, fresh weight and other stress‐related indexes after a freezing treatment. Transcriptome analysis showed that numerous stress‐related genes were differentially expressed in LcFIN1 ‐overexpressing plants, suggesting that LcFIN1 may enhance plant abiotic stress tolerance by transcriptional regulation. Electrophoretic mobility shift assays and CHIP‐qPCR showed that LcCBF1 can bind to the CRT/DRE cis‐ element located in the promoter region of LcFIN1, suggesting that LcFIN1 is directly regulated by LcCBF1. Taken together, our results suggest that LcFIN1 positively regulates plant adaptation response to cold stress and is a promising candidate gene to improve crop cold tolerance.